Microfiber epidermal thermometer (MET) with extraordinary high precision designed for long-term use on hairy skin - Adeela Hanif; Junho Park; Dohui Kim; Jangwon Yoon; Unyong Jeong; Dong Sung Kim (npj Flexible Electronics)
Abstract Long-term epidermal monitoring with wearable electronics is often hindered on hairy skin due to hair regrowth, which disrupts the skin-device interface and can damage the device. Here, we introduce a high-precision microfiber epidermal thermometer (MET) designed for deformation-insensitive, durable, reliable performance on hairy skin. MET utilizes a stretchable fiber (~340 µm diameter), smaller than average hair follicle spacing, enabling conformal contact without interference from growing hair. Localized nanofiber reinforcement on a microfiber and temperature-sensing layer on localized region create a strain-engineered architecture, allowing MET to achieve strain-insensitive temperature detection. MET demonstrates stable operation under repeated strains (up to 55%) and delivers exceptional precision, with a temperature resolution of 0.01 °C, even during body movements. It accurately tracks physiological temperature fluctuations and provides consistent measurements over 26 days of continuous wear, remaining unaffected by hair regrowth or motion. These results highlight MET as a robust platform for long-term temperature monitoring on hairy skin.